Perbandingan Tingkat Nomophobia Mahasiswa Ditinjau Berdasarkan Jenis Kelamin - Nina Fitriyani; Nurul Albertin; RA Murti Kusuma (Universitas Kanjuruhan Malang, 2019)
The purpose of this research is to know the description of the comparative level of nomophobia on students. The methods used in this research is descriptive quantitative survey form. Measured sampling consists of approximately 303 students in some universities that are easily and readily available for research. An instrument used to use the likert scale. Based on the results of research conducted by the author, shown with data analysis and discussion of the writer can then conclude that the picture on the extent of nomophobia students have differences: based on the author's research that has been done be aware that the level of nomophobia men with women including into the high category because it has achieved 50% with the percentage of 40% of men and 60% with 303 responden. In women suggests that there are different between the percentage of men with women.